Benzylpenicillin plus an aminoglycoside versus meropenem in neutropenic lymphoma and leukaemia patients with a suspected bacterial infection: a randomized, controlled trial. (March 2017) - Torfoss, D.; Fladhagen, T.; Holte, H.; Brinch, L.; Schjesvold, F.H.; Fløisand, Y.; Nyquist, E.; Dalgaard, J.; Meyer, P.; Lehmann, A.K.; Hammerstrøm, J.; Skjelbakken, T.; et al.
Abstract: Objectives: In Norway, initial treatment of febrile neutropenia (FN) has traditionally been benzylpenicillin plus an aminoglycoside. Internationally, FN is often treated with a broad-spectrum β-lactam antibiotic. We aimed to compare these two regimens in a prospective, randomized, trial in patients with lymphoma or leukaemia with an expected period of neutropenia ≥7 days, and a suspected bacterial infection. Methods: Adult neutropenic patients with lymphoma or leukaemia, and a suspected bacterial infection, were randomized for treatment with benzylpenicillin plus an aminoglycoside or meropenem. The primary endpoint was clinical success, defined as no modification of antibiotics and clinical stability 72 h after randomization. Results: Among 322 randomized patients, 297 proved evaluable for analyses. Fifty-nine per cent (95% CI 51%–66%), (87/148) of the patients given benzylpenicillin plus an aminoglycoside were clinically stable, and had no antibiotic modifications 72 h after randomization, compared with 82% (95% CI 75%–87%), (122/149) of the patients given meropenem (p <0.001). When the antibiotic therapy was stopped, 24% (95% CI 18%–32%), (36/148) of the patients given benzylpenicillin plus an aminoglycoside, compared with 52% (95% CI 44%–60%), (78/149) of the patients given meropenem, had no modifications of their regimens (p <0.001). In the benzylpenicillin plus an aminoglycoside arm, the all-cause fatality within 30 days of randomization was 3.4% (95% CI 1.2%–7.9%), (5/148) of the patients, compared with 0% (95% CI 0.0%–3.0%), (0/149) of the patients in the meropenem arm (p 0.03). Conclusion: Clinical success was more common in FN patients randomized to meropenem compared with the patients randomized to benzylpenicillin plus an aminoglycoside. The all-cause fatality was higher among the patients given benzylpenicillin plus an aminoglycoside.